Individualized exercise prescription for athletes using a construct-based model - Hegedus, E. J.; Hegedus, S. R.; Wright, A.; Dickson, T.; Stern, B. D. (Sports Medicine, 2022)
Rehabilitation professionals prescribe exercise regularly with the goals of decreasing pain, increasing function, and returning athletes to competition. To maximize the effect of an exercise intervention, the program must be individualized and in context for the athlete considering biopsychosocial aspects of care. Current models of exercise prescription may not be ideal considering that less than 50% of injured athletes return to their pre-injury level. Advice on exercise prescription has been offered in the past, but the paradigms are either not user friendly or user friendly but linear, based on phases of recovery. As such, there is a need for a more flexible exercise prescription paradigm that should improve the individuality of exercise prescription. In this Current Opinion, we offer a user-friendly construct-oriented paradigm designed to facilitate the creation of individualized exercise programs for athletes.